Returns to Education Quality for Low-Skilled Students: Evidence from a Discontinuity - Canaan, Serena; Mouganie, Pierre (Journal of Labor Economics, 2018)
This paper studies the labor market returns to higher-education quality for low-skilled students. Using a regression discontinuity design, we compare students who marginally pass and marginally fail the French high school exit exam on the first attempt. Threshold crossing leads to an improvement in quality but has no effect on quantity of higher education pursued. Specifically, students who marginally pass are more likely to enroll in STEM majors and postsecondary institutions with better peers. Marginally passing also increases earnings by 12.5% at the ages of 27–29.